Pengenalan Rumah Adat Sumatera Utara Menggunakan Augmented Rality Berbasis Android - Parasian DP Silitonga; Destri Gultom; Irene Sri Morina (Jurnal ICT : Information Communication & Technology, 2020)
This study aims to increase knowledge through multimedia-based learning by utilizing information technology, namely Augmented Reality (AR) in knowing the types of traditional houses in North Sumatra province.Augmented reality (AR), is the appearance of real-world dimensions with virtual worlds in real time. In contrast to virtual reality which completely replaces what is in the real world, augmented reality is a process of adding or completing virtual reality. Augmented reality depicts a three-dimensional object on a marker as a unique pattern so that it can be recognized by the object processing application. Augmented reality can be used to create a more interactive recognition environment where users can interact directly with objects in cyberspace. The augmented reality application produced in this study was developed using the Vuforia Software Development Kit. In addition, the resulting application runs on the android mobile platform, which is expected to provide easy access for users